Teacher Stress: A Psychobiological Approach to Stressful Interactions in the Classroom - Wettstein, Alexander; Schneider, Sandra; grosse Holtforth, Martin; La Marca, Roberto (Frontiers in Education, 2021)
Teachers report elevated levels of stress and psychosomatic illnesses compared to other professions. Teacher stress has far-reaching consequences on their health outcomes, the student's motivation, and the economy. However, research on teacher stress relies mainly on self-reports, hence, assesses stress on purely subjective perception. Personal or subjective aspects can strongly influence these measures, and biological stress may even be unnoticed. It is, therefore, necessary to include both subjective and objective measures to investigate stress, preferably in real-life situations. This review aims to demonstrate the importance of a psychobiological ambulatory assessment (AA) approach to investigate teacher stress, in contrast to purely subjective measures. We discuss classroom disruptions as the primary stress factor within the classroom and how a multimethod AA approach using psychological measures while simultaneously recording classroom disruptions and biological stress reactions of teachers would enable a much deeper understanding of stressful transactional processes taking place in the classroom that has not been achieved before.